A-184 Increased Cerebrospinal Fluid Levels of Amyloid Following Traumatic Brain Injury are Associated with Confrontation Naming Performance. (17th August 2022) - Howard, Erica; Moody, Jena N; Prieto, Sarah; Hayes, Jasmeet P
Abstract: Objective: To explore whether beta-amyloid (AB) overproduction is implicated in the relationship between traumatic brain injury (TBI) and Alzheimer's disease (AD), we compared cerebrospinal fluid (CSF) levels of AB in individuals with a TBI history versus controls (CTRLs) and related CSF AB levels to confrontation naming performance, a pseudo-marker for preclinical AD. Method: We selected 113 non-impaired Veterans (TBI=57, CTRL=56) from the Alzheimer's Disease Neuroimaging Initiative-Department of Defense database with available Boston Naming Test (BNT) data and CSF measures for three AB peptides (AB-42, AB-40, AB-38). Analysis of covariance (ANCOVA) compared CSF AB levels between groups adjusting for age. Spearman's correlations related CSF AB levels to BNT performance. Three separate mediation models explored the relationship between TBI and BNT performance with each AB peptide as a mediator. Results: The TBI group had higher CSF AB-40 (F=5.20, p=0.02) and AB-38 (F=3.78, p=0.05) levels than the CTRL group, but groups did not significantly differ in CSF AB-42 levels (p>0.1). BNT was negatively correlated with all three AB peptides (AB-42: rho=-0.28, p=0.003; AB-40: rho=-0.20, p=0.03; AB-38: rho=-0.19, p=0.05). Mediation models showed a significant indirect effect of TBI on BNT performance through AB-40 (B=-0.16, 95% CI [-0.391, -0.007], PM = 0.54). TBI positively affected AB-40 levels (B=0.45, p=0.02), and AB-40 levels, in turn, negatively affected BNT performance (B=-0.14, p=0.04). Indirect effects of TBI on BNT performance with AB-42 or AB-38 as mediators were not significant. Conclusions: TBI may increase risk of AD-related cognitive decline through AB overabundance in the brain, as evidenced by elevated CSF AB levels, particularly AB-40.